Anti-mafia itineraries in southern Italy: the ship of legality as an avant-garde educational laboratory (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The article reports the results of a research conducted on the experience of the so-called "Ship of legality", through the direct voice of the protagonists – teachers and students – who participated in the project in the Southern Italy schools. In addition to reconstructing, through oral sources, the biographical and professional profiles of teachers, who were engaged in the project, the article review the forms of activism carried out in the schools by analysing the number of entries to the Falcone Call between 2006 and 2021.
Keywords: ship of legality; education of lawfulness; school; teaching methodology; Anti-Mafia Movement